Critical care capacity in Haiti: A nationwide cross-sectional survey - Losonczy, Lia I.; Barnes, Sean L.; Liu, Shiping; Williams, Sarah R.; McCurdy, Michael T.; Lemos, Vivienne; Chandler, Jerry; Colas, L. Nathalie; Augustin, Marc E.; Papali, Alfred (PloS one, 2019)
Critical illness affects health systems globally, but low- and middle-income countries (LMICs) bear a disproportionate burden. Due to a paucity of data, the capacity to care for critically ill patients in LMICs is largely unknown. Haiti has the lowest health indices in the Western Hemisphere. In this study, we report results of the first known nationwide survey of critical care capacity in Haiti. Nationwide, cross-sectional survey of Haitian hospitals in 2017-2018. Haiti. All Haitian health facilities with at least six hospital beds. Electronic- and paper-based survey. Of 51 health facilities identified, 39 (76.5%) from all ten Haitian administrative departments completed the survey, reporting 124 reported ICU beds nationally. Of facilities without an ICU, 20 (83.3%) care for critically ill patients in the emergency department. There is capacity to ventilate 62 patients nationally within ICUs and six patients outside of the ICU. One-third of facilities with ICUs report formal critical care training for their physicians. Only five facilities met criteria for a Level 1 ICU as defined by the World Federation of Societies of Intensive and Critical Care Medicine. Self-identified barriers to providing more effective critical care services include lack of physical space for critically ill patients, lack of equipment, and few formally trained physicians and nurses. Despite a high demand for critical care services in Haiti, current capacity remains insufficient to meet need. A significant amount of critical care in Haiti is provided outside of the ICU, highlighting the important overlap between emergency and critical care medicine in LMICs. Many ICUs in Haiti lack basic components for critical care delivery. Streamlining critical care services through protocol development, education, and training may improve important clinical outcomes.